Transformasi Karakteristik Jasa Rumah Sakit di Era Digitalisasi Pelayanan Kesehatan: Tinjauan Literatur dan Implikasi Manajerial - Fazari Maulidina Cahyani; Finisia Noviyanti; Firman Wirasto Saptahadi; Hartanto Hartanto; A. Rohendi (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The rapid expansion of digital health technologies has fundamentally reshaped hospital service delivery; however, limited conceptual studies have examined how digitalization transforms the core characteristics of services. This study aims to analyze how digital transformation alters the fundamental service dimensions of hospitals intangibility, heterogeneity, inseparability, and perishability and to identify their managerial implications. A systematic and thematic literature review was conducted using peer-reviewed articles indexed in Scopus, PubMed, ScienceDirect, and Google Scholar published between 2015 and 2024. From the initial search results, relevant studies were screened based on predefined inclusion and exclusion criteria, and the selected articles were synthesized thematically. The findings indicate that digital technologies such as electronic medical records, telemedicine, hospital information systems, and artificial intelligence enhance service transparency and traceability, reduce variability through process standardization, enable remote interaction beyond physical boundaries, and improve capacity management through real-time monitoring. These transformations require strategic alignment, digital competency development, and strengthened information governance to ensure service quality and data security. This study contributes conceptually by integrating service marketing theory with digital health transformation and provides practical insights for hospital managers in designing adaptive and patient-centered service strategies.